Strategi Budaya Sonorik Reflektif dalam Komposisi Musik Rene Hu: Representasi Identitas Institusional melalui Autoetnografi Artistik - Kadek Indra Wijaya; Esyaf Sedik; Noak Msen; Yohana Mikaela Kelanit; Thobias Rumbino Fonataba; Steven Lazareth Kawer; I Putu Agus Eko Sattvika (Lembaga Pengembangan Kinerja Dosen, 2026)
The creation of institutional signature music is typically understood as a technical compositional process intended to accompany a performance. This study aims to elucidate how the music of the Rene Hu dance is constructed as a medium for representing institutional identity through the integration of local wisdom and organizational values. Utilizing an artistic autoethnographic approach, this research positions the creative experience of the composer as a reflective data source analyzed through both thematic and conceptual lenses. The findings indicate that the composition of Rene Hu music emerges from the interaction of cultural, ecological, and institutional dimensions, all mediated by the composer’s reflection as a strategic agent. The integration of Sentani traditions, the soundscape of Mount Cycloop, and digital technology forms a sonoric identity that represents both cultural legitimacy and the vision of the Papua Province Language Center. This study formulates the Reflective Sonoric Cultural Strategy Model, which explains the mechanisms of identity negotiation within the composition of such signature music. The novelty of this research lies in its conceptualization of institutional music as an arena for identity negotiation analyzed through the composer’s creative journey. This research offers a conceptual framework applicable to the creation of similar representational musical works.